Pengaruh Budaya Organisasi, Beban Kerja dan Kepuasan Kerja Terhadap Kinerja Pegawai Pada Dinas Koperasi, Usaha Kecil dan Menengah dan Perdagangan Kota Probolinggo - Eni Nofita Sari; Muhammad Syarif Hidayatullah Elmas; Junaidi ‎ (Universitas Panca Marga, 2024)
This research was conducted on DKUMP Probolinggo City with the aim of knowing the influence of organizational culture, workload, job satisfaction on employee performance at the Office of KUMP Probolinggo City. The type of research used is quantitative, through independent variables (free) Organizational Culture, Workload and Job Satisfaction as well as the dependent variable (tied) Employee performance. The population in this study were DKUMP employees from Probolinggo City (non ASN). The samples taken were 82 employees. The sampling technique used is non probability sampling with purposive sampling technique. Sources of data in this study come from primary and secondary data. data collection using interviews, questionnaires, documentation and processed with data analysis methods in the form of validation tests, reliability, classical assumption tests, normality tests, multiple linear regression analysis, coefficient of determination and hypothesis testing. The results showed that there was a significant influence between organizational culture (X1), workload (X2), job satisfaction (X3) simultaneously on performance (Y) where the calculated f value was 51.649. Then from the test it shows that organizational culture variable (X1) has a significant effect on performance (Y) with t count 3.675, workload variable (X2) has a significant effect on performance (Y) with t count 2.852 and job satisfaction variable (X3) has a significant effect on Performance (Y) with t count 2.921. The dominant test shows that the organizational culture variable (X1) has a dominant influence on performance (Y) with a standardized beta coefficient of 0.321.